Reflection as a Tool for Personal and Professional Development. - Aaron, Laura; Hicks, Joel; McKnight, Angela; Andary, Joseph (Radiologic Technology)
Purpose To evaluate the use of reflection by radiography students and radiographers. Methods Radiography students and radiographers completed reflection assignments as a part of capstone courses, which were taken near graduation in an entry-level bachelor of science radiography program (BSRS) and a bachelor of science completion program (registered technologist to BSRS). Responses were evaluated to determine achievement of predetermined outcomes and objectives. Results There were 115 students and 25 radiographers who completed the reflection assignments. The mean scores of radiography students and current radiographers were measured to address the achievement of 2 student learning outcomes. Student learning outcome 1 contained 6 objectives, and it was found that radiographers scored significantly higher than did radiography students on 5 of the 6 objectives. Student learning outcome 2 had 5 objectives, and it was found that radiographers also scored significantly higher on each objective. Discussion Although most radiography students and radiographers were able to link theory with practice through reflection to some degree, it was discovered that radiographers scored significantly higher than did radiography students in 10 of the 11 objectives, using these same outcome assessments. The results seem to indicate that the additional clinical experiences of radiographers, compared with radiography students, enabled radiographers to better reflect on their previous learning and apply it to new and different situations. Despite differences in the ability to critically reflect on previous learning, however, it is thought that students and technologists can use what they learn through reflection for continued professional development. In addition, educators can use this information to identify areas for improvement in their programs. Conclusion Radiographers and radiography students were able to apply knowledge gained through critical reflection in clinical practice. Compared with radiography students, radiographers have a greater capacity to reflect critically. The ability for greater reflection is partly due to having more clinical experiences to use as a frame of reference for reflection. Therefore, guided and critical reflection is useful for students and radiographers to apply theory learned to the clinical environment.